A new generalized variant of the deteriorated PSS preconditioner for nonsymmetric saddle point problems. (15th July 2022) - Shao, Xin-Hui; Meng, Hui-Nan
Abstract: To solve nonsymmetric saddle point problems, a new generalized variant of the DPSS ( NGVDPSS ) preconditioner is proposed. The invertibility of the NGVDPSS preconditioner, the convergence of the NGVDPSS iteration method and some properties of the corresponding preconditioned matrix are presented. The degree of minimal polynomials of the preconditioned matrix is obtained. Simultaneously, the algorithm implementation of the NGVDPSS preconditioner is discussed. Numerical experiments are performed to illustrate the availability of the new preconditioner.